The Madden‐Julian Oscillation in an Aquaplanet‐Like General Circulation Model With and Without Continents - Surajit Das; Debasis Sengupta; Arindam Chakraborty (Journal of Advances in Modeling Earth Systems, 2019)
Abstract We have conducted experiments with the Community Atmospheric Model version 5.1 configured as an aquaplanet, with the sun at March equinox, in order to study how the model Madden‐Julian oscillation (MJO) responds to (i) the introduction of continents and (ii) realistic sea surface temperature (SST) distribution. Model results are compared with ERA‐Interim reanalysis and analyzed in terms of the moist static energy (MSE) budget to study the growth and propagation of MJO. With idealized zonally symmetric SST, the aquaplanet model produces a double Intertropical Convergence Zone (ITCZ) and an MJO‐like mode with variance at intraseasonal (30‐ to 96‐day) periods and zonal wave number 1. When we introduce continents with realistic orography and interactive surface temperature, soil moisture, and albedo, the variance of MJO is mainly confined to zonal wave numbers 1 and 2 but reduced by a factor of 3 due to weaker boundary layer moisture convergence. With prescribed climatological January SST boundary condition (which includes Indo‐west Pacific warm pool) in the presence of continents, model MJO variance is enhanced and distributed across zonal wave numbers 1 to 5, in closer agreement with observation. Thus, the presence of land by itself is not enough, but realistic SST distribution is necessary for improved space‐time characteristics of model MJO. Both in simulations and ERA‐Interim data, meridional and vertical advection of MSE promotes eastward movement of MJO. In the model experiments, meridional advection of low‐level MSE anomaly is most significant in the vicinity of the ITCZ, indicating the importance of processes that determine the location of (single or double) ITCZ.